Radiological Characteristics of Patients With Anti-MDA5–Antibody-Positive Dermatomyositis in 18F-FDG PET/CT: A Pilot Study - Cao, Heng; Liang, Junyu; Xu, Danyi; Liu, Yinuo; Yao, Yinan; Sun, Yiduo; He, Ye; Lin, Jin (Frontiers in Medicine, 2021)
Objective: To elucidate the 18F-fluorodeoxyglucose (FDG) PET/CT characteristics and its prognostic value in the patients with anti-melanoma differentiation associated protein 5 antibody positive (anti-MDA5+) dermatomyositis (DM). Methods: This retrospective cross-sectional study included 26 patients with anti-MDA5+ DM and 43 patients with anti-MDA5 negative (anti-MDA5–) idiopathic inflammatory myopathy (IIM) who were examined by 18F-FDG PET/CT from January 1, 2017 to December 31, 2020. The maximum standardized uptake value (SUVmax) of multiple organs and other clinical characteristics of the patients were measured and analyzed. Results: Compared with the anti-MDA5– group, the patients in the anti-MDA5+ group showed higher bilateral lung SUVmax (p = 0.029), higher SUVmax of spleen (p = 0.011), and bone marrow (p = 0.048). Significant correlations between the spleen SUVmax and serum ferritin levels (r = 0.398, p < 0.001), erythrocyte sedimentation rate (ESR) (r = 0.274, p = 0.023), platelet count (r = −0.265, p= 0.028), myositis disease activity assessment score (r = 0.332, p = 0.005), bone marrow SUVmax (r = 0.564, p < 0.001), and bilateral lung SUVmax (r = 0.393, p < 0.001) were observed. Conclusion:18F-FDG PET/CT was found valuable in quantifying the pulmonary focal inflammation and potentially unveil the distinctive characteristics and pathophysiological mechanisms in the patients with anti-MDA5+ DM.